Identifying and mitigating against potential seafloor and shallow drilling hazards at a complex Gulf of Mexico Deepwater site using HR3D seismic and AUV data. Issue 4 (1st June 2017) - Kassarie, Kern; Mitchell, Stephen; Albertin, Martin; Hill, Andrew; Carney, Robert
ABSTRACT: This paper presents an integrated and iterative approach to the identification and understanding of seafloor and shallow geohazards at a complex geologic setting in the deepwater Gulf of Mexico. The approach, focusing on geophysical data gathering and processing, allowed continuous improvement in the understanding of individual geohazard risks ahead of any eventual selection of wildcat drilling locations. The progressive development of increased image resolution has included the use of the following data types: exploration 3D, autonomous underwater vehicle seabed clearance, short‐offset 3D, a full‐waveform inversion velocity model, HR3D acquisition, HR3D, autonomous underwater vehicle high‐resolution sonar, and seabed photographic transects. Data have assisted in revealing the presence and the understanding of, numerous seafloor and sub‐seafloor geologic features that could potentially affect the choice of well location, well trajectory, and final drilling practices. Features that have been defined have included active benthic communities, widespread seafloor faulting, multi‐scale active seabed expulsion features, slope‐failure scarps, mass transport complexes, shallow gas, and various effects from the presence and transmission of shallow overpressure towards the seafloor. The final, integrated geologic model that is developed will allow selection of well surface locations and trajectories that meet local regulatory requirements for safe drilling and environmental protection, as well as the adoption of safe drilling practices to mitigate identified hazards.